2007
DOI: 10.1177/009145090703400306
|View full text |Cite
|
Sign up to set email alerts
|

Advances in the Determination of Alcohol and Other Drug Consumption during Pregnancy: A Study of 900 Births in Montevideo, Uruguay

Abstract: A study was performed in Uruguay to estimate the prevalence of drug consumption during pregnancy. The study consisted of a survey and biological samples to validate the responses and investigate information concerning risks involved in drug consumption during pregnancy. The survey consisted of 900 face-to-face interviews performed within 48 hours after birth. Perinatal registries were taken from hospital archives. Nine hundred meconium samples were tested for alcohol, tobacco, illegal drugs, and tranquilizers.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 31 publications
1
5
0
Order By: Relevance
“…AUDIT: Alcohol Use Disorders Identification Test; FAEE: fatty acid ethyl esters; n/a: not available; SES: socio-economic status. a Levels of increased sensitivity may not total percentage figures obtained via meconium testing divided by percentage figures obtained via self-reports due to rounding errors. b Pichini et al [44] reported results for two study sites (Italy and Spain). c Reported “daily” consumption. d Hutson et al [37] and Magri et al [38,39] were published in iteration. e Derauf et al [40,41] are dual publication. f Excludes 5 women who reported alcohol use during the first trimester only.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…AUDIT: Alcohol Use Disorders Identification Test; FAEE: fatty acid ethyl esters; n/a: not available; SES: socio-economic status. a Levels of increased sensitivity may not total percentage figures obtained via meconium testing divided by percentage figures obtained via self-reports due to rounding errors. b Pichini et al [44] reported results for two study sites (Italy and Spain). c Reported “daily” consumption. d Hutson et al [37] and Magri et al [38,39] were published in iteration. e Derauf et al [40,41] are dual publication. f Excludes 5 women who reported alcohol use during the first trimester only.…”
Section: Resultsmentioning
confidence: 99%
“…Nine studies on the prevalence of PAE, obtained via maternal self-reports and meconium testing (Hutson et al [ 37 ] and Magri et al [ 38 , 39 ] were published in iteration, and Derauf et al [ 40 , 41 ] are dual publications), were identified from the literature. Data on the prevalence of PAE, obtained via maternal self-reports and meconium testing, were available from only six countries: Canada [ 15 , 42 ], Germany [ 43 ], Italy [ 44 , 45 ], Spain [ 36 , 44 , 46 ], Uruguay [ 37 - 39 ], and the United States [ 40 , 41 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the predicted prevalence for Argentina (12.9%; 95%CI: 11.1%–14.7%) is more reasonable. Similarly, a study utilizing meconium testing in Montevideo, Uruguay, reported that 43.5% of samples tested positive for fatty acid ethyl esters above standard cut-off levels (i.e., 2 n mol/g) among women from low- and mid-to-low socioeconomic levels (63).…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have reported the prevalence of Fetal Alcohol Syndrome (FAS; the most severe and visibly identifiable form of FASD) in South America. Specifically, it has been reported to be 0.1% among the general population of Brazil and Uruguay (11, 12). However, the prevalence of FAS and partial FAS among children in care in Chile has been reported to be much higher: 15% among those in foster homes (13), and 16% among those in child welfare custody and homes for those with mental deficiencies (14).…”
mentioning
confidence: 99%